2019
DOI: 10.1186/s12879-019-4514-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of hepatitis C virus in liver disease patients in Botswana: a retrospective cross-sectional study

Abstract: BackgroundHepatitis C virus (HCV) infection is a major cause of chronic liver disease globally. Direct acting antivirals (DAAs) have proven effective in curing HCV. However, the current standard of care (SOC) in Botswana remains PEGylated interferon-α (IFN-α) with ribavirin. Several mutations have been reported to confer resistance to interferon-based treatments. Therefore, there is a need to determine HCV genotypes in Botswana, as these data will guide new treatment guidelines and understanding of HCV epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…3,14 The anti-HCV seroprevalence in this study was higher (4.3%) than the previously reported rates of 0.49% -0.8% in HIVinfected patients in Botswana, likely because of the fact that the enrolled patients had liver disease. 17,18,52 Higher anti-HCV seroprevalence between 6% and 22.5% has been reported from similar studies in Africa and Asia. 5,10,12,26 Similar to other studies in this region a slightly higher prevalence (57%) was found in females.…”
Section: Discussionmentioning
confidence: 81%
“…3,14 The anti-HCV seroprevalence in this study was higher (4.3%) than the previously reported rates of 0.49% -0.8% in HIVinfected patients in Botswana, likely because of the fact that the enrolled patients had liver disease. 17,18,52 Higher anti-HCV seroprevalence between 6% and 22.5% has been reported from similar studies in Africa and Asia. 5,10,12,26 Similar to other studies in this region a slightly higher prevalence (57%) was found in females.…”
Section: Discussionmentioning
confidence: 81%
“…19,27,28 In this study, we have confirmed that only two genotypes circulating in Kilifi County; this can form a basis for more targeted control for the 2 subtypes in the region.Hepatitis C Virus diversity is very essential in response to antiviral therapy. 21,29 More severe liver disease and more elevated liver enzymes have been highly associated with HCV genotype 1. 30 The endemicity of HCV genotypes in some areas is revered with multiplicity and diversity of subtypes and strains.…”
Section: Discussionmentioning
confidence: 99%
“…20 (Zymo, Irvine, CA, USA) according to the manufacturer's protocol to eliminate unincorporated primers and dNTPs. 21 The purified amplicons were sequenced with Big Dye kit, and the ABI PRIS M 3100 genetic analyzer (Applied Biosystems) according to manufacturer's instructions.…”
Section: Polymerase Chain Reaction (Rt-pcr) and Sequencing Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV genotype 5 was originally identified in South Africa [15,16], where it represents 35-60% of all HCV genotypes [16][17][18][19][20]. However, pockets of genotype 5 infections have been reported in France, Spain, Syria, Greece, Botswana, Ethiopia, India, and Belgium [21][22][23][24][25][26][27][28][29][30][31][32]. There is paucity of data on resistance-associated variants (RAVs) in South Africa.…”
Section: Introductionmentioning
confidence: 99%